Composition for repairing meniscus and meniscus replacement application thereof
By loading GDF and elevated microspheres in mesoporous silicon nanoparticles, the problems of microenvironment inflammation and oxidative stress in meniscus damage treatment were solved, effective differentiation and regeneration of chondrocytes were achieved, and the effect of meniscus functional reconstruction was significantly improved.
Patent Information
- Application Number
- CN202411685354.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-11-22
AI Technical Summary
The prior art is difficult to effectively improve the harsh inflammatory and oxidative stress microenvironment in the treatment of meniscus injury, resulting in poor regeneration of cartilage tissue.
A microsphere loaded with growth differentiation factor (GDF) and elevated is developed, combined with the "core-shell" co-delivery nanocarrier constructed by mesoporous silicon nanoparticles. By continuously releasing elevated elevated elevated chestic differentiation process, improving the microenvironment and promoting meniscus functional reconstruction.
It realizes the continuous release of GDF and emodin in the inflammatory and oxidative stress environment, coordinates the harsh microenvironment, promotes chondrocyte differentiation and regeneration, and significantly improves the functional reconstruction effect of meniscus.
Smart Images

Figure CN119564941A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a biomaterial, in particular to a composition loaded with differentiation-promoting active molecules for promoting cartilage differentiation and regeneration, and application in medical devices. Background Art
[0002] The meniscus is a crescent-shaped fibrocartilaginous tissue with major biological functions, including shock absorption and providing overall mechanical stability to the knee joint. Meniscus injuries are common in sports, and current clinical treatment strategies for severe meniscus injuries requiring total meniscus replacement include meniscus allograft transplantation (MAT) and meniscus prosthesis repair. However, their long-term therapeutic effects are not significant due to the mismatch in graft size and shape. Recently, the development of cartilage tissue engineering has provided a new strategy for clinical meniscus replacement, namely, the use of seed cells combined with scaffold materials to achieve three-dimensional cartilage regeneration in vivo. For the regeneration of complex shapes and heterogeneous structures of cartilage, our research group proposed a reinforced concrete tissue engineering strategy combined with 3D printing for ear, nose, trachea and meniscus applications.
[0003] Despite remarkable progress in cartilage tissue regeneration, successful tissue regeneration at the defect site requires the creation of a favorable regenerative microenvironment. The poor microenvironment caused by chronic inflammation and oxidative stress or acute trauma in patients during clinical surgery seriously hinders tissue regeneration, making the development of innovative strategies for cartilage tissue engineering still a challenging and rare clinical breakthrough. Especially in meniscectomy, the cruciate ligaments are cut, the joint surface is worn, and the meniscus defect site leads to strong oxidative stress and inevitable inflammatory stimulation. Therefore, it is necessary to develop a new construction strategy to achieve synergistic regulation of correcting the poor microenvironment and promoting cartilage tissue regeneration.
[0004] It has been reported that growth differentiation factor (GDF) can effectively promote the differentiation of fibroblasts into fibrochondrocytes. However, the lack of a sustained release system has resulted in unsatisfactory long-term effects.
[0005] Therefore, it is necessary to develop a technology that combines the improvement of the adverse microenvironment of inflammation and oxidative stress with satisfactory reconstruction of meniscus function. Summary of the invention
[0006] One object of the present invention is to provide a composition for inflammation and oxidative stress to promote the chondrogenic differentiation process of cells.
[0007] Another object of the present invention is to provide a composition for inflammation and oxidative stress, promoting cell differentiation into chondrogenesis, and facilitating the reconstruction of meniscus function.
[0008] Another object of the present invention is to provide a hydrogel containing microspheres, load the microspheres into the hydrogel, provide a cell growth environment, facilitate the active substances released from the microspheres to regulate the cell chondrogenic differentiation process, promote cartilage growth and repair, and promote cell chondrogenic differentiation.
[0009] Another object of the present invention is to provide an application for meniscus replacement, wherein microspheres loaded with GDF and emodin are applied to a scaffold to improve inflammation and oxidative stress in the microenvironment, promote cell chondrogenic differentiation, and facilitate meniscus function reconstruction.
[0010] A composition comprising growth differentiation factor and rhamnosine improves inflammation and oxidative stress in microenvironment and promotes the chondrogenic differentiation process of cells.
[0011] Another composition is microspheres loaded with growth differentiation factors and emodin, which improve inflammation and oxidative stress in the microenvironment and promote the process of cell chondrogenic differentiation.
[0012] Another composition is a "core-shell" structure constructed of mesoporous silicon nanoparticles, which carries growth differentiation factors and rhamnosus, improves inflammation and oxidative stress in the microenvironment, and promotes the process of cell chondrogenic differentiation.
[0013] Another composition is a "core-shell" structure constructed of mesoporous silicon nanoparticles, in which the core contains rhein, and growth differentiation factors can be releasably bound to the nuclear surface, improving inflammation and oxidative stress in the microenvironment and promoting the process of cell chondrogenic differentiation.
[0014] Another composition is a "core-shell" structure constructed of mesoporous silicon nanoparticles, in which the core contains rhein, and growth differentiation factors are grafted to the nuclear surface through reversible disulfide bonds, thereby improving inflammation and oxidative stress in the microenvironment and promoting the process of cell chondrogenic differentiation.
[0015] In vitro experiments showed that sustained-release emodin could effectively regulate macrophage M1 / M2 polarization and maintain a good regenerative microenvironment, while releasing GDF to promote fibrochondrogenic differentiation of fibroblast / chondrocyte seed cells.
[0016] In addition, the particles made from the above-mentioned various compositions are added to a gel composed of methacryloyl hydrogel (GelMA) and chondroitin sulfate methacrylate (CSMA) (denoted as: GC, with a weight ratio of 6:1) to form a cartilage-specific matrix hydrogel, which has good cell compatibility, rheological and mechanical properties, and is also conducive to loading cells, such as: chondrocytes and fibrochondrocytes.
[0017] In order to be suitable for total meniscus replacement, the present invention also provides a PCL scaffold manufactured by 3D printing, which contains chondrocytes and fibroblasts (fibroblasts and chondrocytes are mixed in a ratio of 7:3), GC gel and Em@MSN-GDF, recorded as: Em@MSN-GDF / GC-PCL (wherein the concentration of Em@MSN-GDF contained is 10 μg / mL), which synergistically regulates the cartilage immune microenvironment in total meniscus replacement, synergistically regulates inflammation and oxidative stress, as well as harsh microenvironment and fibrocartilage regeneration, and promotes meniscus cartilage differentiation and molding.
[0018] The microspheres of the present invention first load emodin on dSiO2 silica gel balls, then use hexadecyltrimethylammonium chloride (CTAC) as a template and tetraethylorthosilicate (TEOS) as a silicon source to prepare mesoporous silica microspheres (denoted as: Em@MSN), first add 3-mercaptopropyltrimethoxysilane (MPTMs) to obtain surface thiol-modified microspheres (denoted as: Em@MSN-SH), and then mix with GDF protein to obtain mesoporous silica microspheres loaded with growth differentiation factors and emodin, denoted as: Em@MSN-GDF. The average particle size of the microspheres is: 169±15.37nm, and the Zeta potential is 12.77±1.07mV.
[0019] The microspheres of the present invention were characterized for sustained release within 45 days, with the release rate of GDF reaching 50% and the release rate of emodin approaching 60%.
[0020] It has been verified that the "core-shell" co-delivery nanocarrier (Em@MSN-GDF) provided by the present invention uses mesoporous silica nanoparticles to encapsulate two bioactive compounds: emodin (a natural anti-inflammatory and antioxidant) and growth differentiation factor (GDF), the latter of which is used to promote fibrocartilage differentiation. This dual-drug nanodelivery system provides sustained release of emodin and GDF, synergistically regulates the harsh inflammatory and oxidative environment, and promotes fibrocartilage regeneration in vitro and in vivo.
[0021] In addition, benefiting from the effect of Em@MSN-GDF, the present invention also uses cartilage-specific matrix hydrogel to combine the 3D-printed meniscus-shaped PCL framework with Em@MSN-GDF to construct a meniscus replacement model (scaffold) with enhanced stability, which has the function of synergistically regulating the cartilage immune microenvironment and achieves the successful repair of total meniscus replacement in animals (rabbits). BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1Figure 2 shows the prepared Em@MSN-GDF microspheres and their characterization results; A is a schematic diagram of the preparation process of Em@MSN-GDF microspheres, B is a transmission electron microscope (TEM) image of Em@MSN, Em@MSN-SH and Em@MSN-GDF (scale bar = 100 nm), C is a statistical diagram of the average particle size of Em@MSN, Em@MSN-SH and Em@MSN-GDF, and D is the zet a Potential result diagram, E is the energy dispersive spectroscopy (EDS) image of Em@MSN-GDF (scale bar = 200 nm), F is the percentage of elements in the EDS of Em@MSN-GDF, G is the particle size distribution histogram of Em@MSN-GDF, H is the solid-state nuclear magnetic resonance spectrum of Si of Em@MSN, Em@MSN-SH and Em@MSN-GDF, i is the solid-state nuclear magnetic resonance spectrum of H of Em@MSN, Em@MSN-SH and Em@MSN-GDF, J is the XPS S-2p spectrum of Em@MSN, K is the XPS S-2p spectrum of Em@MSN-SH, L is the XPS S-2p spectrum of Em@MSN-GDF, M is the statistical diagram of the encapsulation rate of rheum officinale, N is the sustained release curve of GDF, and O is the sustained release curve of rheum officinale;
[0023] Figure 2 Preparation and performance characterization diagram of GC and Em@MSN-GDF / GC; A is the bright field photo of the gelation process of GelMA / CSMA (GC) and Em@MSN-GDF / GC under 365nm ultraviolet irradiation, B is the SEM image of GC and Em@MSN-GDF / GC, C is the storage modulus (G') and loss modulus (G") result diagram, D is the compression strain curve, E is the statistical diagram of the expansion ratio of each group, F is the statistical diagram of the degradation rate of each group, G is AM / PI and F-actin (10μg / mL Figure 1 shows the cell staining images of Em@MSN-GDF / GC at 1 day, 4 days, 7 days and 14 days, H shows the cell viability statistics of Em@MSN-GDF / GC at 1 day, 4 days, 7 days and 14 days, I shows the quantitative statistics of live cell counts at 1 day, 4 days, 7 days and 14 days, J shows the quantitative statistics of f-actin fluorescence at 1 day, 4 days, 7 days and 14 days, K shows the CCK-8 detection results of Em@MSN-GDF fibroblasts at 48 hours;
[0024] Figure 3Figure 2 is the result of the in vitro antioxidant and anti-inflammatory effects of Em@MSN-SH and Em@MSN-GDF; A is the ROS fluorescence image after co-culture with Em@MSN or Em@MSN GDF at 1 mM H2O2 for 24 h, B is the fluorescence intensity statistical graph shown in Figure A, C is the relative mRNA statistical graph of GPX1 / GAD(P)H after co-culture with Em@MSN or Em@MSN-GDF at 1 mM H2O2 for 24 h, D is the relative mRNA statistical graph of NQO1 / GAD(P)H after co-culture with Em@MSN or Em@MSN-GDF at 1 mM H2O2 for 24 h, E is the flow cytometry result of M1 and M2 polarization of macrophages in each group, and F is the M1 (CD86 + ) Macrophage statistics, G is M2 (CD206 + ) macrophage statistics, H is the relative mRNA statistics of TNF-α / GAD(P)H when RAW264.7 cells were co-cultured with Em@MSN or Em@MSN-GDF under the action of 100 ng / mL LPS for 24 h, I is the relative mRNA statistics of IL-6 / GAD(P)H when RAW264.7 cells were co-cultured with Em@MSN or Em@MSN-GDF under the action of 100 ng / mL LPS for 24 h, J is the antioxidant and anti-inflammatory principle diagram of Em@MSN-GDF;
[0025] Figure 4Figures are the results of the effects of GDF on fibroblasts in vitro and in vivo; A is a schematic diagram of the Transwell co-culture system, B is a crystal violet staining image of fibroblasts cultured in the upper chamber and chondrocytes cultured in the lower chamber using an 8μm Transwell culture chamber, after 24 and 72 hours of co-culture, C is an Alcian blue staining image of fibroblasts cultured in the upper chamber using a 0.4μm Transwell culture chamber, cultured alone or co-cultured with chondrocytes in the lower chamber, after 7 days, D is a statistical graph of the expression of COLⅡ related mRNA in fibroblasts analyzed by qRT-PCR, E is a statistical graph of the expression of ACAN related mRNA in fibroblasts analyzed by qRT-PCR, F is a statistical graph of the expression of α-SMA related mRNA in fibroblasts analyzed by qRT-PCR, G is a statistical graph of the expression of SOX9 related mRNA in fibroblasts analyzed by qRT-PCR, and H is a Western blotting of COLⅡ, ACAN, α-SMA and SOX9 related proteins in fibroblasts treated with 100ng / mL GDF for 7 days. Blotting electrophoresis images, I is the bright field photo of the implant, J is the photo of the surgical process of nude mice implanted with GC hydrogel, K is the general photo of the mouse 6 weeks after implantation, L is the photo of the general morphology of the implants in each group 6 weeks after implantation, M is the immunofluorescence staining (blue) of HE, SO, COL II (green) and α-SMA (red) and cell nuclei in FBs, FBs7 / CHs3, FBs3 / CHs7 and CHs groups 6 weeks after implantation (scale bar = 100 μm), N is the statistical graph of the fluorescence density of COL II in each group, O is the statistical graph of the fluorescence density of α-SMA in each group (FBs: fibroblasts, FBs7 / CHs3: fibroblasts 7 and chondrocytes 3; FBs3 / CHs7: fibroblasts 3 and chondrocytes 7; CHs: chondrocytes);
[0026] Figure 5 Figure 1 is the in vivo evaluation result of Em@MSN-GDF / GC-PCL in chondrogenesis; A is a photographic image of a cell-loaded GC-PCL implant, B is a bright field photograph of the gross morphology of GC-PCL, Em@MSN / GC-PCL and Em@MSN-GDF / GC-PCL implants after 6 weeks, C is a COL II (green), α-SMA (red), HE and SO staining image of GC-PCL, Em@MSN / GC-PCL and Em@MSN-GDF / GC-PCL groups after 6 weeks (cell nuclei are blue, scale bar = 100 μm), D is a statistical graph of the Young's modulus results of the GC-PCL group, Em@MSN / GC-PCL group and Em@MSN-GDF / GC-PCL group 6 weeks after surgery, E is a statistical graph of the fluorescence density of COLⅡ, and F is a statistical graph of the fluorescence density of α-SMA;
[0027] Figure 6Figure 1 is the in vivo evaluation result of meniscus replacement and repair; A is a bright field photograph of the crescent-shaped Em@MSN-GDF / GC-PCL implant containing FBs7 / CHs3 cells, B is a photograph of the surgical process of implanting the crescent-shaped prosthesis in the New Zealand rabbit medial meniscus defect model, C is the MRI images of the PCL group and the Em@MSN-GDF / GC-PCL group 6 and 12 weeks after surgery, D is a bright field photograph of the gross morphology of the knee joint 12 weeks after surgery, E is a bright field photograph of the gross morphology of the crescent-shaped implant 12 weeks after surgery, F is the HE, SO, COL II, COL I, α-SMA (red), VEGF (red) and VMF (green) staining of the Em@MSN-GDF / GC-PCL group, G is a quantitative statistical graph of α-SMA fluorescence intensity, H is a quantitative statistical graph of VEGF fluorescence intensity, I is a quantitative statistical graph of VWF fluorescence intensity, and J is a statistical graph of ICRS scores 12 weeks after implantation. DETAILED DESCRIPTION
[0028] The technical solution of the present invention is described in detail below with reference to the accompanying drawings. The embodiments of the present invention are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention is described in detail with reference to the preferred embodiments, it should be understood by those skilled in the art that the technical solution of the invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present invention, which should be included in the scope of the claims of the present invention.
[0029] The various test methods used in the following examples of the present invention are specifically described as follows:
[0030] 1) Cell culture
[0031] 2 cm × 2 cm skin tissue sections were collected from adult New Zealand white rabbits. The tissue was digested in 2% neutral protease at 4°C overnight and then washed twice with PBS. Subsequently, the tissue was digested in 2% collagenase for 4 hours to obtain fibroblasts. Subsequently, the cells were cultured and expanded in an incubator at 37°C with 5% CO2. Second and third generation fibroblasts and chondrocytes were used in this study. The cells were cultured in high glucose DMEM basal medium supplemented with 10% fetal bovine serum and 1% penicillin-streptomycin.
[0032] 2) Preparation and characterization of Em@MSN-GDF
[0033] Synthesis of Em@MSN microspheres: Based on previous studies, rhein (S30748, Yuanye, Shanghai, China) was accurately weighed and dissolved in 5 ml of water. Then 35.7 mL of ethanol and 0.785 mL of ammonia solution were added and stirred at room temperature for 10 minutes. Then, 1 mL of TEOS (T819505, Macklin, Shanghai, China) was added and stirred at room temperature for 1 h. The mixture was centrifuged at 10000 rpm for 20 min, and the precipitate was washed 3 times with ethanol and resuspended with 20 mL of deionized water to obtain a dSiO2 aqueous solution.
[0034] 4 g of CTAC (A610332, Sangon Biotech, Shanghai, China) was weighed and dissolved in 40 mL of water. 400 μL of triethanolamine (TEA) (A600970, Sangon Biotech, Shanghai, China) was added and stirred at room temperature for 1 h, then 20 mL of dSiO2 aqueous solution prepared previously was added, stirred at 80 °C for 1 h, and 300 μL of TEOS was added dropwise. Once the reaction cooled to room temperature, 1272 mg of Na2CO3 was added to the mixture and etching was performed for 30 minutes. The product was subjected to a series of washing steps, starting with water, followed by 1% sodium chloride-methanol solution, and finally washed three times with anhydrous ethanol. This process produced Em@MSN microspheres encapsulating rhamnosine.
[0035] Synthesis of Em@MSN-SH microspheres: 300 mg of Em@MSN microspheres were dispersed in 5 ml of deionized water, 200 μL of MPTMs (M812736, Macklin, Shanghai, China) were added, stirred at room temperature for 2 h, centrifuged at 12,000 rpm for 20 min, and washed with anhydrous ethanol for 3 times to obtain Em@MSN-SH microspheres.
[0036] Synthesis of Em@MSN-GDF microspheres: 10 mg of Em@MSN-SH microspheres were dispersed in 1 mL of deionized water. Then 1 μg of GDF protein (CSB-YP009349HU, CUSABIO, Wuhan, China) was added and stirred at room temperature for 24 h. The resulting precipitate was centrifuged at 15,000 rpm for 20 min to obtain Em@MSN-GDF microspheres.
[0037] 3) Rhein encapsulation efficiency and GDF loading
[0038] The encapsulation efficiency of emodin at 440 nm was determined by UV spectrophotometry (UV-5100). First, the UV absorbance of the supernatant before stirring and centrifugation was measured, and then the UV absorbance of the supernatant after stirring and centrifugation was measured. The encapsulation efficiency of emodin was calculated using the relevant formula. The drug loading of GDF was determined using an ELISA kit (CSB-EL009349HU, CUSABIO, Wuhan, China). 10mM DTT was used to dissociate the protein bound to Em@MSN-GDF. After centrifugation at 12000rpm for 10 minutes, the supernatant was collected for ELISA detection.
[0039] 4) Preparation and characterization of hydrogels
[0040] To prepare the standard hydrogel, 60 mg of GelMA (R201A2, SinoBioPrint, Shanghai, China), 10 mg of CSMA (R203A1, SinoBioPrint, Shanghai, China) and 2 mg of photoinitiator (lithium phenyl-2,4,6-trimethylbenzoylphosphonate, LAP) (G101A2, SinoBioPrint, Shanghai, China) were dissolved in 1 ml of PBS. The solution was heated to 60 °C until completely dissolved and then irradiated under 365 nm light for 7 s to form a photocrosslinked hydrogel.
[0041] 5) Rheological analysis
[0042] The aqueous gel solutions were tested using a Thermo HAAKE MARS 60 rheometer with parallel plate geometry at 25 °C (25 mm diameter). Dynamic rheological experiments were performed by exposing the samples to light (365 nm, 20 mW / cm 2 ) for 60 s, and the time sweep oscillation test lasted for 120 s, with a strain of 10% (CD mode), a frequency of 1 Hz, and a gap of 0.5 mm. It can be observed that the gel point of the storage modulus (G') will exceed the time of the loss modulus (G').
[0043] 6) In vitro swelling and degradation test
[0044] The swelling and degradation tests of the hydrogels were performed using the specific gravity method as described in previous studies. The initial hydrogel wet weight was recorded as W0, and the wet weight of the hydrogel after 24 h was recorded as Ws. The swelling ratio was defined as Ws / W0×100% (n=4), and the initial hydrogel wet weight was recorded as Wd, and the remaining hydrogel wet weight after soaking in the enzyme solution (1% w / v collagenase) was recorded as Wt. The degradation rate was defined as (Wd-Wt) / Wd×100% (n=4).
[0045] 7) Mechanical properties test
[0046] The samples (n=3) were prepared into cylinders with a diameter of 10 mm and a height of 2 mm. The mechanical properties of the hydrogels were determined using a dynamic mechanical analyzer (Instaston-5542, Canton, USA). -1 The compression rate is 2000 until the compression depth reaches 80% of the initial height. Then, the elastic modulus is calculated from 10% to 20% of the initial strain-stress curve.
[0047] 8) qRT-PCR and Western Blotting Analysis
[0048] Total RNA was extracted with chloroform according to the previously described method and reverse transcribed using the Takara kit. SYBR Green was used for gene quantification. The ΔCT method was used to calculate the mRNA expression of related genes, including cartilage-related genes (COLⅡ, ACAM, SOX9, α-SMA), oxidative stress-related genes (NQO1, GPX1), and inflammation-related genes (TNF-α, IL-6). Total protein was extracted using RIPA lysis buffer (P0013B, Beyotime, Shanghai, China), followed by SDS-PAGE, membrane transfer, and related protein band development.
[0049] 9) Cytotoxicity and biocompatibility
[0050] Cells were seeded in 96-well plates at a density of 3000 cells per well and treated with drugs at a specific ratio. 10 μL of CCK-8 reagent (CK04, Dojindo, Shanghai, China) was added to each well and incubated in the dark for 2 h. The absorbance was measured at 450 nm. Fibroblasts and chondrocytes were added at a ratio of 7:3 (3×10 26 Cells) were inoculated into 2 ml of hydrogel containing Em@MSN-GDF. Cells were cultured in culture dishes for 1 day, 4 days, 7 days, and 14 days. Cell viability was assessed using the Calcein-AM / PI (live / dead) staining kit (C542, Dojindo, Shanghai, China) according to the manufacturer's instructions. F-actin and cell nuclei were stained with Actin-Tracker (C2205S, Beyotime, Shanghai, China) and DAPI (C1006, Beyotime, Shanghai, China), respectively. Fluorescence images were collected using a Leica fluorescence microscope (Leica THUNDER DMI8), and fluorescence intensity was quantified using Image J software.
[0051] 10) Antioxidant test
[0052] RAW264.7(1×10 5 Cells were seeded in 6-well plates. Cells were stimulated with 1 mM H2O2 to induce oxidative stress, and then treated with Em@MSN and Em@MSN-GDF for 24 h. DCFH-DA (1:1000) (S0033S, Beyotime, Shanghai, China) was added and incubated at 37°C for 2 h. Fluorescence intensity was observed and photographed under a Leica THUNDER DMI8 microscope, and fluorescence intensity was quantified using Image J software.
[0053] 11) Anti-inflammatory experiment
[0054] RAW264.7 cells (density 1×10 5 Cells were inoculated on a 6-well cell slide. The cells were stimulated with 100 ng / mL LPS for 16 h, and then treated with Em@MSN and Em@MSN-GDF for 24 h. The supernatant was collected and the cells were incubated with CD86 antibody and CD206, respectively, and analyzed by flow cytometry.
[0055] 12) Transwell and Alcian staining
[0056] This experiment used Transwell culture chambers with different pore sizes to study the effect of chondrocytes on fibroblasts. First, fibroblasts were implanted into the cavity using a Transwell culture chamber with a pore size of 8 μm and co-cultured with chondrocytes. After 24 and 72 hours of co-culture, the migration of fibroblasts was observed using crystal violet staining. Crystal violet staining was used to detect the number and migration ability of fibroblasts.
[0057] At the same time, fibroblasts and chondrocytes were implanted into different culture chambers using a Transwell culture chamber with a pore size of 0.4 μm and cultured for 7 days. After the culture period, the content of glycosaminoglycans (GAGs) in fibroblasts was detected by Alcian blue staining, which is an important marker of cartilage differentiation. Alcian blue staining to detect GAG content can indicate whether fibroblasts are differentiating into chondrocytes.
[0058] 13) In vivo evaluation of cell co-culture ratio
[0059] Cells (FBs, FBs7:CHs3=7:3, FBs3:CHs7=3:7, CHs) were seeded into the hydrogel at a density of 4x107 cells / mL to form discs with a diameter of 1 cm. These discs were then implanted subcutaneously into nude mice. After 6 weeks, histological staining was performed to determine the optimal cell co-culture ratio for promoting cartilage regeneration.
[0060] 14) Validation of in vivo cartilage regeneration and chondrogenesis by bioprinting
[0061] To evaluate cartilage regeneration in vivo, the REGENOVO WS) developed a 3D bioprinting framework that mixed fibroblasts and chondrocytes in a ratio of 7:3 (5×10 7 cells / mL) and coated with GelMA / CSMA hydrogel. This cell-loaded hydrogel was integrated into a polycaprolactone (PCL) scaffold, where the PCL scaffold was created by 3D bioprinting technology with a size of 10×10×2mm and a gap structure of 2mm. The scaffolds assembled with cells and hydrogel were implanted subcutaneously in nude mice. After 6 weeks, cartilage formation and regeneration were evaluated to verify the potential of different cell ratios to promote cartilage regeneration in vivo. .
[0062] 15) Establishment and repair of meniscus defect model
[0063] One-month-old New Zealand white rabbits were used to collect fibroblasts and chondrocytes for autologous implantation. First, a PCL meniscus-shaped scaffold with 2mm holes was printed using 3D printing technology. The hydrogel was then mixed with cells and Em@MSN-GDF and injected into the scaffold. During surgery, a PCL scaffold or Em@MSN-GDF-PCL was used to replace the medial meniscus. MRI scans were performed at 6 and 12 weeks after surgery to monitor meniscus regeneration, and tissue specimens were collected at 12 weeks for histological staining to evaluate the degree of meniscus regeneration.
[0064] 16) Histological and immunohistochemical analysis
[0065] The cells were fixed with 4% paraformaldehyde for 2 days, embedded in paraffin, and sectioned into 6 μm thick sections. The sections were further stained with hematoxylin and eosin (HE), safranin (SO), COL II, and COL I according to the manufacturer's protocol to evaluate the regenerated tissue architecture.
[0066] In addition, after antigen retrieval and serum blocking, the sections were incubated with monoclonal antibodies against COL I (1:300), COL II (1:50), α-SMA (1:500), VEGF (1:200), and VMF (1:100) at 4°C overnight, followed by incubation with fluorescent secondary antibodies for 1 hour. The staining results were observed under a fluorescence microscope. Finally, a semiquantitative histological scoring system was used to further evaluate meniscus regeneration.
[0067] 17) Statistics
[0068] All quantitative data are expressed as mean ± standard deviation (SD). All statistics were tested by Student's t test, and p value < 0.05 was considered to be significantly different. In the graphs shown, * indicates P < 0.05, ** indicates P < 0.01, and *** indicates P < 0.001.
[0069] Example 1 Preparation and characterization of Em@MSN-GDF.
[0070] Three types of mesoporous silica microspheres: Em@MSN, Em@MSN-SH and Em@MSN-GDF were prepared using hexadecyltrimethylammonium chloride (CTAC) as template and tetraethylorthosilicate (TEOS) as silicon source. Figure 1 A shows the preparation process of Em@MSN-GDF microspheres. The microstructural characteristics of the samples were studied using transmission electron microscopy (TEM), such as Figure 1 As shown in B, the synthesis of Em@MSN, Em@MSN-SH and Em@MSN-GDF was observed and analyzed. The image shows that there are evenly distributed pores on the surface of Em@MSN, indicating the successful synthesis of hollow mesoporous silica. At the same time, the surfaces of both Em@MSN-SH and Em@MSN-GDF samples were observed to have an irregular coating, which covered the pores on the surface and showed a clear but uneven coating. The results of this coating layer show that surface functionalization and GDF protein loading have a significant effect on the nanoparticles. The uneven distribution of surface functional groups and the different loaded proteins lead to uneven thickness of the surface coating. In addition, Figure 1 C shows the particle size analysis of three mesoporous silica nanodrug delivery systems, with average particle sizes of 151±23.69nm, 168±18.04nm, and 169±15.37nm, respectively. The Zeta potentials were -36.76±0.70mV, -40.07±1.05mV, and 12.77±1.07mV ( Figure 1 D). The results show that with the coupling of thiol-modified Em@MSN and GDF, the particle size of mesoporous silica gradually increases, and the potential of Em@MSN-GDF is increased by about 49 mV compared with that of Em@MSN.
[0071] Energy dispersive spectroscopy (EDS) images ( Figure 1 E) and electron microscopy images before and after thiol modification and protein loading, which clearly demonstrated the successful synthesis of the mesoporous silica nanoparticle drug delivery system Em@MSN-GDF. The results showed that Em@MSN-GDF contained C (52.45%), N (0.81%), O (21.15%), Si (21.49%) and S (4.11%) elements ( Figure 1 F), the elements are evenly distributed inside the nanomaterial, and the particle size of Em@MSN-GDF is 170nm ( Figure 1 G). In addition, to further verify the success of thiol modification and protein on the mesoporous silica surface, we performed 29Si NMR ( Figure 1 H) and 1HNMR ( Figure 1 I) Analysis. Figure 1In the H NMR spectrum, there is a peak at 3.5ppm, and the peak of Em@MSN-GDF is reduced, indicating that the thiol modification and protein loading of mesoporous silica are successful. The peak at -65ppm in the 29Si NMR spectrum further confirms the success of thiol modification. In addition, X-ray photoelectron spectroscopy (XPS) was used to identify the functional groups in the nanomaterials. The XPS S-2p spectra of Em@MSN, Em@MSN-SH, and Em@MSN-GDF are shown in Figure 2. Figure 1 J. Figure 1 K. Figure 1 L. The peaks at 162.5eV and 164eV correspond to SH and SS bonds. After modification with silane coupling agent, the peak of the new element S is Figure 1 K and Figure 1 L, indicating that Em@MSN-SH was successfully synthesized. Comparing the changes in element peaks during the synthesis process, it was found that the SS peak area of Em@MSN-GDF increased significantly, indicating that the SS content increased relatively, which may be due to the loading of protein. In addition, there was no significant difference in the encapsulation efficiency of rhein in the three nanomaterials, which was about 14% ( Figure 1 M). Finally, we have GDF( Figure 1 N) and rhein ( Figure 1 O) The sustained release profile at 45 days was characterized, and the release rate of GDF reached 50%, and the release rate of emodin was close to 60%.
[0072] In summary, these results have confirmed that emodin and GDF can achieve a long-term sustained release effect in the Em@MSN-GDF mesoporous silica nanoparticle drug delivery system. This extended release is essential for achieving long-term therapeutic effects in high oxidative stress and inflammatory environments, such as those encountered after meniscectomy. The synergistic release of the two drugs helps to modulate the cartilage immune microenvironment.
[0073] Example 2 Physicochemical and biological evaluation of Em@MSN-GDF / GC.
[0074] This example evaluates the physicochemical properties, biocompatibility and cell proliferation promoting effect of Em@MSN-GDF / GC hydrogel. Figure 2 As shown in A, at 365nm and 20mW / cm 2 Under ultraviolet irradiation, the hydrogel quickly transformed from solution to gel state within 60s. Observe the SEM images of GC and Em@MSN-GDF / GC after freeze-drying ( Figure 2 B), and found that both have microporous structures, and the pore size changes are not obvious. Rheological analysis shows that the hydrogel undergoes a large amount of photopolymerization within 60s to form a gel ( Figure 2C), there was no significant difference in the storage modulus (G') and loss modulus (G") between GC and Em@MSN-GDF / GC (P>0.05).
[0075] In addition, there was no significant difference in compressive stress between GC and Em@MSN-GDF / GC ( Figure 2 D). Swelling and degradation experiments showed that there was no significant difference in swelling rate and degradation rate between GC and Em@MSN-GDF / GC ( Figure 2 E and Figure 2 F). These results indicate that the introduction of Em@MSN-GDF did not significantly change the microporous structure, mechanical strength, and compressive properties of the GC hydrogel, indicating that the system maintained the same structure and mechanical properties as the original GC hydrogel. This stability is critical for the application of tissue engineering scaffolds, as the hydrogel must maintain mechanical support during degradation. In addition, the rapid photocrosslinking process (less than 60 seconds) facilitates rapid operation in clinical applications, which is particularly important for reducing intraoperative contamination and minimizing cell damage.
[0076] In addition, the biocompatibility of Em@MSN-GDF / GC was evaluated by live / dead staining, cell morphology analysis, and cell proliferation studies. Figure 2 As shown in G, AM-PI staining and F-actin staining showed that FBs and CHs cells were able to proliferate and spread well within the Em@MSN-GDF / GC matrix, indicating that Em@MSN-GDF / GC effectively supported cell growth and proliferation. Figure 2 H shows that the cells showed high viability after 14 days of in vitro culture. From day 1 to day 14, the cell viability gradually increased, as shown in Figure 2 I. At the same time, F-actin fluorescence statistics showed that the proliferation of cells increased gradually during the 14-day observation period, and from the 1st day to the 14th day, the proliferation of cells showed an increasing trend ( Figure 2 J).
[0077] In order to further confirm the promoting effect of Em@MSN-GDF on cell proliferation level, cytotoxicity experiments were also performed. Figure 2 K showed that Em@MSN-GDF had no obvious toxicity to cells at concentrations of 10 μg / mL and 20 μg / mL. In order to protect cells from the potential harmful effects of drug toxicity, a concentration of 10 μg / mL was used in subsequent cell experiments.
[0078] The results showed that Em@MSN-GDF / GC hydrogel had good cell compatibility and enabled cells to survive, spread, and proliferate in vitro, providing strong support for meniscus regeneration.
[0079] Example 3 Evaluation of Antioxidant and Anti-inflammatory Effects in Vitro
[0080] 1mM H2O2 was added to FBs7 / CHs3 cells to induce elevated reactive oxygen species (ROS) levels. After 24 hours of treatment with 1mM H2O2 combined with Em@MSN and Em@MSN-GDF, the intracellular ROS level was assessed using the DCFH-DA (1:1000) probe. The results showed that the fluorescence intensity of the Em@MSN and Em@MSN-GDF treatment groups was significantly reduced compared with the H2O2 treatment group alone ( Figure 3 A and Figure 3 B), and the mRNA expression levels of related antioxidant genes glutathione peroxidase 1 (GPX1) and NAD(P)H quinone dehydrogenase 1 (NQO1) were also significantly decreased ( Figure 3 C and Figure 3 D). These results indicate that rhamnosin released from Em@MSN and Em@MSN-GDF can effectively scavenge ROS. This antioxidant effect is particularly important in the context of meniscus regeneration, as continued ROS accumulation can damage cells and impair their repair capacity.
[0081] In addition, to investigate the role of Em@MSN and Em@MSN-GDF in the polarization of macrophages to anti-inflammatory phenotype, we used lipopolysaccharide (LPS) as a pro-inflammatory agent and analyzed the macrophage polarization results by flow cytometry ( Figure 3 E. Figure 3 F and Figure 3 G). Compared with the control group, the proportion of M1 (CD86+) macrophages in the LPS-treated group was significantly increased. In contrast, the proportion of M1 macrophages in the Em@MSN and Em@MSN-GDF-treated groups was significantly decreased, and the proportion of M2 (CD206+) macrophages in the Em@MSN and Em@MSN-GDF-treated groups was significantly increased. This suggests that Em@MSN and Em@MSN-GDF promote the transition of macrophages to an anti-inflammatory phenotype, which helps to inhibit excessive inflammation and support tissue repair. To further verify this finding, we measured the relative mRNA expression levels of inflammatory factors, including interleukin 6 (IL-6) and tumor necrosis factor-α (TNF-α), in macrophages using qRT-PCR. Figure 3 H and 3I showed that the relative expression levels of proinflammatory factors in the Em@MSN and Em@MSN-GDF treatment groups were significantly reduced compared with the LPS treatment group. This anti-inflammatory effect is particularly important for improving the postoperative microenvironment, as persistent inflammation can hinder meniscus regeneration and lead to cartilage degeneration. Figure 3 J provided a brief overview of the antioxidant and anti-inflammatory effects of Em@MSN-GDF.
[0082] The above results indicate that the antioxidant and anti-inflammatory functions of Em@MSN and Em@MSN-GDF are attributed to the release of emodin, which promotes the differentiation of macrophages toward an anti-inflammatory phenotype.
[0083] Example 4 Extracellular matrix and GDF promote chondrogenic differentiation of FBs
[0084] Transwell chambers with different pore sizes were used for characterization to further study the effects of extracellular matrix secreted by chondrocytes on fibroblasts. Figure 4 A shows the experimental setup, where fibroblasts were cultured in the upper chamber and chondrocytes in the lower chamber. The effect of chondrocytes on the migration ability of fibroblasts was studied using a Transwell chamber with a pore size of 8 μm. Fibroblasts were stained with crystal violet after 24 and 72 h of co-culture. Figure 4 B. The increase in staining intensity indicates that the extracellular matrix of chondrocytes significantly affects the migration of fibroblasts.
[0085] Transwell chambers with a pore size of 0.4 μm were used to study the effect of chondrocytes on the chondrogenic differentiation of fibroblasts. Figure 4 As shown in C, fibroblasts co-cultured with chondrocytes showed higher Alcian blue staining compared with fibroblasts cultured alone. These results suggest that the extracellular matrix derived from chondrocytes has a favorable effect on the chondrogenic differentiation of fibroblasts.
[0086] Similarly, GDF shows great potential in the field of tissue engineering, especially in promoting stem cell differentiation and chondrogenesis. Studies have shown that GDF can effectively induce fibroblasts to differentiate into fibrochondrocytes.
[0087] 100ng / mL GDF protein was cultured into chondrocytes to further study the function of GDF in promoting fibroblast differentiation into fibrocartilage. After 7 days of in vitro culture, we used Western blotting and qRT-PCR to analyze the expression of cartilage-related genes in FBs (fibroblasts) and FBs+GDF groups. Figures D, E, F, and G show that compared with the FBs group, the mRNA levels of COL II, ACAN, α-SMA, and SOX9 in the FBs+GDF group were increased. Compared with the FBs group, the protein levels of COL II, ACAN, α-SMA, and SOX9 in the FBs+GDF group were also increased ( Figure 4 H). Western blotting and qRT-PCR results showed that GDF has the ability to promote the differentiation of fibroblasts into fibrochondrocytes. These results indicate that both the extracellular matrix of chondrocytes and GDF affect the chondrogenic differentiation of fibroblasts.
[0088] In order to better promote fibrocartilage regeneration, GDF was combined with the function of chondrocyte extracellular matrix. Different ratios of fibroblasts and chondrocytes were subcutaneously implanted into nude mice to study the feasibility of fibrocartilage regeneration with different cell ratios under GDF treatment. Figure 4 As shown in I, 30 million cells were mixed with 100 ng / mL GDF in GC hydrogel and formed into a 10 mm diameter disk, which was then implanted subcutaneously in nude mice. Figure 4 J shows the surgical procedure for implanting the intervertebral disc under the skin of nude mice. Figure 4 L shows the initial formation of cartilage-like samples after 6 weeks of implantation with different cell ratios. The tissue transparency of the FBs7 / CHs3 group was similar to that of the FBs3 / CHs7 group. Histological analysis further confirmed that HE and SO staining showed that the regenerated cartilage showed similar levels of typical cartilage-specific lacunar structures between the FBs7 / CHs3 group and the FBs3 / CHs7 group ( Figure 4 M). In the FBs7 / CHs3 cell ratio group, the level of tissue expression of COLⅡ was the same as that in the FBs3 / CHs7 group ( Figure 4 N). In addition, the expression level of α-SMA in the FBs7 / CHs3 group was higher than that in the FBs3 / CHs7 group ( Figure 4 O). These results suggest that effective cartilage regeneration can be achieved with only 30% chondrocyte proportion during GDF treatment.
[0089] Example 5 Evaluation of Em@MSN-GDF in in vivo chondrogenesis
[0090] In order to improve the stability and mechanical strength of cartilage regeneration, a rectangular PCL scaffold with a length of 1 cm, a width of 1 cm, and a height of 2 mm was produced by 3D printing technology, and the hole length was 2 mm. Figure 5 As shown in A. GC hydrogel containing 50 million / mL FBs7 / CHs3 cells was implanted into PCL scaffold to form an implant.
[0091] The grafts were divided into three groups (GC-PCL group, Em@MSN / GC-PCL group and Em@MSN-GDF / GC-PCL group) and then implanted subcutaneously in nude mice to further study the promoting effect of GDF on chondrogenic differentiation. After 6 weeks of implantation, the morphology of the implants in the three groups remained basically unchanged ( Figure 5 B).
[0092] Then, HE staining, SO staining, COL II and α-SMA immunofluorescence staining were performed ( Figure 5 C), mechanical testing of subcutaneous implant tissue was performed after 6 weeks. Figure 5As shown in D, there was no significant difference in Young's modulus between the Em@MSN / GC-PCL group and the Em@MSN-GDF / GC-PCL group, but both were significantly higher than the GC-PCL group. Statistical analysis of the fluorescence intensity of COLⅡ and α-SMA showed that there was no significant difference in the expression of COLⅡ between the GC-PCL group and the Em@MSN / GC-PCL group. However, compared with the GC-PCL group and the Em@MSN / GC-PCL group, the expression level of COL II in the Em@MSN-GDF / GC-PCL group was significantly higher ( Figure 5 E). In addition, compared with the GC-PCL group and the Em@MSN / GC-PCL group, the expression level of α-SMA in the Em@MSN-GDF / GC-PCL group was significantly increased ( Figure 5 F).
[0093] The above results show that the cartilage phenotype of the Em@MSN-GDF / GC-PCL group exhibits superior characteristics than that of the GC-PCL and Em@MSN / GC-PCL groups. This is mainly attributed to the sustained release of GDF, which is conducive to fibrocartilage differentiation and the formation of functional cartilage matrix. By this method, the Em@MSN-GDF / GC-PCL group not only exhibits enhanced biocompatibility and mechanical properties, but also shows stronger potential in promoting chondrocyte differentiation and cartilage matrix production.
[0094] Example 6 Meniscus replacement and in vivo repair evaluation
[0095] This example further verifies the feasibility of Em@MSN-GDF for meniscus regeneration. First, meniscectomy and replacement surgery were performed on New Zealand rabbits, and a half-moon-shaped polycaprolactone (PCL) scaffold was prepared using 3D bioprinting technology. Fibroblasts and chondrocytes were loaded on the scaffold in a ratio of 7:3 and combined with Em@MSN-GDF / GC hydrogel containing 10μg / mL Em@MSN-GDF powder. The cell density was set at 60 million cells / mL. The mixture was then UV cross-linked (365nm) and injected into the PCL scaffold ( Figure 6 A).
[0096] These scaffolds were implanted into the New Zealand rabbit meniscus defect model. The surgical procedure was as follows: Figure 6 B. PCL stent was used as the control group, and MRI imaging of the knee joint was performed at 6 and 12 weeks after surgery ( Figure 6 C) Observe the cartilage regeneration. 12 weeks after surgery, the replaced medial meniscus successfully formed a structure similar to the normal meniscus ( Figure 6 D and Figure 6E). Further histological analysis showed that the meniscus in the Em@MSN-GDF / GC-PCL group was not only very similar to the normal meniscus in morphology, but also showed regional specificity in cell phenotype and extracellular matrix deposition, which was consistent with the collagen heterogeneity of the normal meniscus ( Figure 6 F).
[0097] Fluorescence quantitative analysis of α-SMA, VEGF, and VWF in the PCL and Em@MSN-GDF / GC-PCL groups showed that the expression levels of α-SMA, VEGF, and VWF in the Em@MSN-GDF / GC-PCL group were significantly higher than those in the PCL group. In addition, there were significant differences in the vascular distribution between the lateral and medial sides of the Em@MSN-GDF / GC-PCL group, which was consistent with the vascular distribution of the normal meniscus ( Figure 6 G. Figure 6 H and Figure 6 I).
[0098] Finally, the articular cartilage was evaluated according to the International Cartilage Repair Society (ICRS) cartilage lesion classification 55, and the PCL group had more severe cartilage damage ( Figure 6 I). In summary, the meniscus regeneration effect of the Em@MSN-GDF / GC-PCL group was significantly better than that of the PCL group, which was close to the characteristics of the normal meniscus.
[0099] In summary, the effect of Em@MSN-GDF / GC-PCL group in meniscus regeneration was significantly better than that of PCL group, and its characteristics were similar to those of normal meniscus. This result indicates that the combination of bio-3D printing technology and GDF drug delivery system can effectively enhance the regeneration process of meniscus. Specifically, the release of Em@MSN-GDF promoted cell proliferation and differentiation, resulting in the regenerated meniscus showing favorable characteristics in terms of morphology, cell phenotype and extracellular matrix deposition.
Claims
1. A composition, characterized in that Including growth differentiation factors and rhamnosus, it improves inflammation and oxidative stress in the microenvironment and promotes the process of cell chondrogenic differentiation.
2. The composition according to claim 1, characterized in that It is in the form of microspheres, which contain growth differentiation factors and rhein.
3. The composition according to claim 1, characterized in that The invention comprises a "core-shell" structure constructed by mesoporous silicon nanoparticles, wherein the rhamnosin is loaded in the core and the growth differentiation factor is releasably bound to the surface of the core.
4. The composition according to any one of claims 1 to 3, characterized in that Also included are gels composed of GelMA and CSMA.
5. The composition according to claim 4, characterized in that The weight ratio of GelMA to CSMA was 6:
1.
6. The composition according to claim 4, characterized in that Also includes chondrocytes and fibroblasts.
7. The composition according to claim 6, characterized in that Also included is PCL, wherein the PCL is made into a scaffold and at least one of the following components is added therein: "Core-shell" microspheres, the core contains the emodin, and the growth differentiation factor is releasably bound to the core surface; GelMA and CSMA composed of gel; and Chondrocytes and fibroblasts.
8. The composition according to claim 1, characterized in that Application in the manufacture of medical devices for meniscus replacement.
9. The use according to claim 8, characterized in that The medical device is a stent, with PCL as the frame, and also includes at least one of the following components: "Core-shell" microspheres, the core contains the emodin, and the growth differentiation factor is releasably bound to the core surface; GelMA and CSMA composed of gel; and Chondrocytes and fibroblasts.
10. A medical device, characterized in that A composition comprising any one of claims 1 to 6.
Citation Information
Patent Citations
Composite material and preparation method and application thereof in decalcified bone matrix scaffold
CN110812531A
Human fat extracellular matrix membrane as well as preparation method and application thereof
CN116036355A
Controlled release of biologically active compounds
US20090060979A1
Method for improving cartilage repair and / or preventing cartilage degeneration in a joint
US20100215731A1
Controlled nutrient delivery to pancreatic islets using a novel mesoporous silica-based nanoparticle platform
US20220401397A1
Cited By
Composition for repairing meniscus, nano-particles, hydrogel material and preparation method and application thereof
CN121754724A